Simple Extractive Colorimetric Determination of Oxaprozin by Acid-Dye Complexation Methods in Solid Dosage Form - M. Ganesh; B. Thangabalan; Rahul Patil; Swastika Ganguly; T. Sivakumar (E-Journal of Chemistry)
A simple and sensitive extractive spectrophometric method has been described for the assay of oxaprozin (OXA) either in pure form or in pharmaceutical solid dosage form. The developed method involves formation of colored chloroform extractable ion-pair complex of OXA with bromocresol green in aqueous acidic medium. The extracted complexes showed absorbance maxima at 421 nm. Beer's law is obeyed in the concentration range of 10-50 μg mL-1. This method has been applied to the determination of drug in commercial tablets. Results of analysis were validated statistically. The excipients present in the formulations do not interfere with the assay procedure.